Changing lenses : a new focus for crime and justice - Zehr, Howard (Christian peace shelf selection., 1990)
Crime victims have many needs, most of which our criminal justice system ignores. In fact, the justice system often increases the injury. Howard Zehr proposes a "restorative" model which is more consistent with experience, with the past, and with the biblical tradition. --from publisher description